2017
DOI: 10.19082/4349
|View full text |Cite
|
Sign up to set email alerts
|

Women's perceptions and experiences of the challenges in the process of male infertility treatment: A qualitative study

Abstract: BackgroundDespite the fact that both men and women are equally subject to infertility, it is usually women who bear the burden of treatment and its consequences, even in cases of male infertility. Therefore, it is more necessary to recognize their health problems in order to help them.AimTo explore women’s perceptions and experiences of the challenges they face in the process of male infertility treatment.MethodsThis qualitative study was conducted during 2014–2015 using content analysis. Thirty semi-structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…23 Taghipour et al, argued that, according to the participating women, the weaknesses in professional communication and services include the medical personnel’s weaknesses in providing information, their tendency to spend little time with infertile couples, their non-responsiveness toward the couples' needs and the semi-dictatorship in their relationship with the patients. 52 It is thus vital for doctors to have greater patience when dealing with their patients, try to understand them and explain the causes of infertility and the right treatments to them. 53 Another need the infertile patients referred to was comprehensive support, highlighting insufficient financial support as one of their main problems after the treatment failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Taghipour et al, argued that, according to the participating women, the weaknesses in professional communication and services include the medical personnel’s weaknesses in providing information, their tendency to spend little time with infertile couples, their non-responsiveness toward the couples' needs and the semi-dictatorship in their relationship with the patients. 52 It is thus vital for doctors to have greater patience when dealing with their patients, try to understand them and explain the causes of infertility and the right treatments to them. 53 Another need the infertile patients referred to was comprehensive support, highlighting insufficient financial support as one of their main problems after the treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited resources in developing countries and the heavy costs of infertility treatment, these medical costs are not covered by supportive organizations such as insurance companies. 52…”
Section: Discussionmentioning
confidence: 99%
“…A review study has shown the psychological consequences following the failure of IVF attempt (8). It was found that only one qualitative study has explored women's experiences of their challenges in the process of male infertility treatment in Iran (25). In addition, to our knowledge, no studies have explored the challenges of failed ARTs in Muslim couples or in Islamic countries.…”
mentioning
confidence: 99%
“…87, As such, most fertility problems and diagnostic and treatment regimes are typically assumed to affect them, 37,87 thereby making the male-factor infertility of less significance. 61 This overemphasis on fertility as a female reproductive health issue portends dire consequences for the 'barren' women. They are usually the most traumatized, disenfranchised and disinherited as a result of their inability to have children, even in proven male-factor infertility marital relationships, and especially in societies with emphasis on childbearing.…”
Section: Rationalementioning
confidence: 99%